The epigenetic encoded memory of the innate immune system - Sun, Sarah (Curr Opin Immunol, 2020)
Stimulation or infection of innate immune cells induces profound epigenetic changes, including the induction of histone modifications and alterations in DNA methylation levels. While some of these changes are rapidly reversible, others appear to be long-lasting, even in mitotic populations, with important functional consequences for the stimulus-experienced cell. Here we discuss the individual contributions of each of the plethora of known epigenetic modifications to the initial transcriptional response to immune activation, their dynamics as cells return to homeostasis, and their contribution to memory of the initial stimulus.